MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI GETARAN DAN GELOMBANG - Hidayati, Citra; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to improve students? learning outcomes abaout vibration and wave by applying the group investigation (GI) model. This research is a quasi-experimental research with a non equivalent control group design research design. This research was conducted at SMP Negeri 21 Pontianak by involving class VIII F with a total of 32 students. Data retrieval of the independent tests, 10 multiple choice questions and 3 essay questions. Based on the result of the independent test sample t N-gain test using SPSS 23 obtained 2-tailed sig of 0.866>0.05 so that Ha is accepted, which means there are differences in learning outcomes between students who are given chances to learn using group investment model compared to the conventional learning, research shows that an increase in student learning outcomes after the implementation of group investigation model is seen from the acquisition of the average score of each material indicator with an increase of 0.8. the group investigation model is effective in improving student learning outcomes in vibration and wave with effect size 2.17 (classified as high). The result of this study are expected to be an alternative in an effort to improve student learning outcomes about vibration and waves. Keyword: Group investigation model, leraning outcomes, vibration and wave.